Identification of a Drosophila gene encoding xylosylprotein beta 4-galactosyltransferase that is essential for the synthesis of glycosaminoglycans and for morphogenesis. - Nakamura, Y.; Haines, N.; Chen, J.; Okajima, T.; Furukawa, K.; Urano, T.; Stanley, P.; Irvine, K.D. (Journal of Biological Chemistry, 2002)
In mammals, the xylosylprotein beta4-galactosyltransferase termed beta4GalT7 (XgalT-1, EC ) participates in proteoglycan biosynthesis through the transfer of galactose to the xylose that initiates each glycosaminoglycan chain. A Drosophila cDNA homologous to mammalian beta4-galactosyltransferases was identified using a human beta4GalT7 cDNA as a probe in a BLAST analysis of expressed sequence tags. The Drosophila cDNA encodes a type II membrane protein with 322 amino acids and shows 49% identity to human beta4GalT7. Extracts from L cells transfected with the cDNA exhibited marked galactosyltransferase activity specific for a xylopyranoside acceptor. Moreover, transfection with the cloned cDNA restored glycosaminoglycan synthesis in beta4GalT7-deficient Chinese hamster ovary cells. In transfectant lysates the properties of Drosophila and human beta4GalT7 resembled each other, except that Drosophila beta4GalT7 showed a less restricted specificity and was active at a wider range of temperatures. Drosophila beta4GalT7 is expressed throughout development, with higher expression levels in adults. Reduction of Drosophila beta4GalT7 levels using expressed RNA interference (RNAi) in imaginal discs resulted in an abnormal wing and leg morphology similar to that of flies with defective Hedgehog and Decapentaplegic signaling, which are known to depend on intact proteoglycan biosynthesis. Immunohistochemical analysis of tissues confirmed that both heparan sulfate and chondroitin sulfate biosynthesis were impaired. Our results demonstrate that Drosophila beta4GalT7 has the in vitro and in vivo properties predicted for an ortholog of human beta4GalT7 and is essential for normal animal development through its role in proteoglycan biosynthesis.